Mainstreaming ESL : case-studies in integrating ESL students into the mainstream curriculum - Clegg, John, 1946- (Multilingual matters (Series), 1996)
"In this book, ESL and mainstream teachers from primary and secondary schools in Australia, Canada, the USA and the United Kingdom, describe how they go about 'mainstreaming'. Well-supplied with examples of teaching materials and pupils' work, their narratives are practical and detailed. At the same time they raise vital questions of school policy which the whole school community must address when launching initiatives of this kind." "The book will be of very practical use to ESL and mainstream teachers, as well as to principals, advisers and those at all levels of the education service who work in multilingual communities. It will also serve as a handbook for teacher-educators and student teachers of any subject who are preparing to work in linguistically diverse classrooms."--Jacket